Impact of environmental pollution and climate changes on the incidence of ST-elevation myocardial infarction. (25th November 2020) - Biondi-Zoccai, G; Frati, G; Gaspardone, A; Mariano, E; Di Giosa, A; Bolignano, A; Dei Giudici, A; Calcagno, S; Scappaticci, M; Sciarretta, S; Valenti, V; Peruzzi, M; et al.
Abstract: Background/Introduction: Several reports have highlighted the detrimental impact of environmental pollution and climate changes on cardiovascular disease. However, detailed analyses aiming at disentangling the differential impact of pollution versus climate are lacking. Most importantly, limited research has focused on ST-elevation myocardial infarction (STEMI), the most severe yet distinctive form of acute coronary syndrome. Purpose/Methods: We aimed at appraising the impact of environmental pollution and climate changes on the incidence of STEMI, analyzing the bivariate and multivariate association between several environmental and atmospheric parameters and the daily incidence of STEMI in two large Italian urban areas. Specifically, we appraised: carbon monoxide (CO), nitrogen dioxide (NO2), nitric oxide (NOX), ozone, particulate matter smaller than 10 μm (PM10) and than 2.5 μm (PM2.5), temperature, atmospheric pressure, humidity, and rainfall. On top of same day association, we appraised STEMI risk 1, 2, and 3 days later. Computations were performed using a multilevel mixed-effects generalized linear model with Poisson likelihood and log link, yielding incidence ratios (95% confidence intervals) and corresponding p values. Results: A total of 4458 days at risk were appraised, 3473 cases of STEMI. Specifically, no STEMI occurred in 1920 (44.8%) days, whereas one or more occurred in the remaining 2365 (55.2%) days. Multilevel modeling identified several pollution and climate predictors of STEMI, either occurring on the same day, or on the following ones. In particular, concentrations of CO (p=0.024), NOX (p=0.039), O3 (p=0.003), PM10 (p=0.033), and PM2.5 (p=0.042) predicted STEMI as early as three day before the event, as well subsequently, and NO predicted STEMI one day before (p=0.010), as well as on the same day. A similar predictive role was evident for temperature and atmospheric pressure (all p<0.05). Notably, strong correlations were evident between same-day temperature, pollutants and climate. Conclusions: The risk of STEMI in the current primary percuntaneous coronary intervention area is strongly associated with pollution and climate features. Most notably, environmental and climate changes can be exploited to predict STEMI risk in the following days. Funding Acknowledgement: Type of funding source: None